Considerations for the study of "incentive hope" and sign-tracking behaviors in humans. (2019) - Pool, Eva R.; Sander, David
Abstract: The amplification of reward-seeking behavior under uncertainty described by Anselme & Güntürkün is based on the animal literature. However, this phenomenon could provide valuable information for the understanding of several dysfunctional human behaviors such as overeating and gambling. Therefore, we formulated some considerations on how the "incentive hope" hypothesis could be tested on a human population.